Parameters of antioxidant barrier in different histopathologic types of pediatric cancers - Stachowicz-Stencel, Teresa; Synakiewicz, Anna; Owczarzak, Anna; Sliwinska, Aleksandra; Lysiak-Szydlowska, Wieslawa; Balcerska, Anna (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : The goal of this study was to evaluate the activities of erythrocyte superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and the levels of glutathione (GSH) and ischemia-modified albumin (IMA), as potential markers in different histopathologic types of pediatric neoplasms. No studies on this subject have been reported to date. Material and methods: SOD, GSH-Px, GSH, and IMA were measured before oncologic treatment in 129 children with neuroblastoma (NB), soft tissue sarcomas (STS), brain tumors, Hodgkin’s disease (HD), and acute leukemias, and in 30 healthy controls. Results : The statistical significance of SOD was observed in patients with brain tumors (median 1840.2 U/g Hb, p = 0.0500). The level of GSH was significantly higher in patients with NB (median 6.38 U/g Hb, p = 0.0031) and leukemias (5.16 U/g Hb, p = 0.0200). IMA was statistically significant in cases of STS, NB, and leukemias compared to healthy children (p = 0.0244, p = 0.0069, and p = = 0.0000, respectively). The activity of GSH-Px was not statistically significant. Conclusions : The antioxidant barrier in all types of pediatric cancers is disturbed. None of the measured parameters was specific enough to represent a reliable marker for any particular histopathologic type of children’s neoplasm.